STAMP-Based Analysis on the Safety Management System of Bus Operators - Ahmad, M.S.; Ariffin, A.H.; Fathi, M.S. (Journal of the Society of Automotive Engineers Malaysia, 2021)
Road accidents involving commercial vehicles are showing an alarming trend from year to year. Ironically the accidents involving heavy vehicles would involve the third party such as cars, motorcycles and other vehicles; due to several factors such as fatigue, speeding, tire defect, road defect, road design issue and risky driving. When occurred, it normally involved higher number of fatalities. Therefore, in order to improve the situation with regards to road accidents involving heavy vehicles, especially buses, a holistic road safety strategy is necessary and vital towards better road safety in the future. This paper aims to understand Safety Management System of bus operators using Systems-Theoretic Accident Model and Processes (STAMP) by analysing three case studies namely Genting, Tapah and Pagoh bus crashes in 2013, 2015 and 2016, respectively. Hazard analysis and causal factors were carried out on the bus operators' Safety Management System by using STPA (Systems- Theoretic Process Analysis) and CAST (Causal Analysis based on STAMP). The results of the analyses showed that the operating process could be revised or redesigned to improve the existing safety system. Moreover, STAMP could be a very useful approach to understand the whole safety system that may involve several complex factors.